The Influence of Investment Knowledge, Minimum Capital, Risk Perception, and Technological Advancement on Students’ Investment Interest in The Capital Market - Nopiyanti, Ni Made; Astiti, Ni Putu Yeni; Mentari, Ni Made Indah; Cahyani, Ni Kadek Intan Dwi; Wulandari, Luh Ayu Trisna; Puspayanti, Ni Luh Ayu; Asih, Ni Nyoman Seri (Journal of International Conference Proceedings, 2025)
Investment is increasingly recognized as an effective alternative to protect and enhance wealth while ensuring financial security in the future. In recent years, the capital market has attracted growing interest among young investors, driven by greater investment knowledge, lower capital requirements, heightened risk awareness, and rapid technological advancement. This study aims to examine the influence of investment knowledge, minimum capital, risk perception, and technological advancement on students’ investment interest in the capital market. The population comprises students from the Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, from the 2021, 2022, and 2023 cohorts. A sample of 98 respondents was determined using proportionate stratified random sampling. Data were analyzed through multiple linear regression. The findings reveal that investment knowledge, risk perception, and technological advancement each have a significant positive effect on investment interest, while minimum capital has a significant negative effect. These results highlight the multidimensional factors shaping student investment behavior. Future studies are recommended to incorporate additional variables, expand the sample size, and extend the research setting beyond a single university to strengthen the generalizability of the findings.